Correlations between different methods of vertical jump and static balance parameters in athletes - Ali Ozkan; Mehmet Goktepe; Mehmet Gunay; Metin Bayram; Sakir Bezcı (Selcuk University, 2016)
This study aims at determining the correlations between different methods of vertical jumping and static balance. A total of 46 male athletes (handball players 14, volleyball players 13, and soccer players 19) were included in the research. For each participant, the following measurements were made respectively: 1) height and weight measurement, 2) 5-minute warm up run, 3) trial measurements so that participants could adjust to the balance platform, 4) Static balance measurements, 5) jumping measurements; and then the procedure was ended. The "Descriptive" test was employed for numerical variables, and descriptive statistics were represented as averages ± standard deviations. Because parametric test assumptions were not met in analysing the independent variables for the participants, Spearman's Moments Multiplication Correlation test was used. In consequence, statistically significant correlations were not found between static jump and counter movement jump - vertical jump methods- and static balance parameters (p gt;0.05). Yet, it may be said that statistically significant correlations are available between drop jump and static balance parameters (p lt;0.05). It was found that there were significant correlations between static balance and drop jump in athletes, but that there were no significant correlations between static jump and counter movement jump.